PERAN DIGITALISASI DALAM MENDUKUNG REFORMASI BIROKRASI: STUDI KASUS PADA INSTANSI PEMERINTAH KOTA TERNATE - Amalia, Rasti; Karianga, Hendra (Jurnal GeoCivic, 2025)
Bureaucratic reform is an urgent need to improve the quality of state civil servants and realize good governance in Indonesia. Bureaucracy is often considered complicated, slow and unprofessional. To overcome this problem, the bureaucracy has intensified the principle of "Digital Serving" in providing public services, because digital services are a demand that will be able to get closer to the community. However, it is necessary to optimize the implementation of Dilan (Digital Serving) because the nature of digital transformation is not only changing ordinary services to online or by building applications in the public and civil society areas evenly.The problem of bureaucratic digitalization above, the purpose of this writing is to see how the digitalization of bureaucracy and public services changes within the scope of the state and civil society as the main elements of the basis of democratization in a modern country. The research method of normative bureaucratic ethics and the institutional organizational approach within the framework of the statute approach, conceptual approach, and analytical approach, Bureaucratic and institutional material tracing techniques using document study techniques, and study analysis using qualitative analysis. bureaucratic digitalization must be fulfilled within the bureaucracy, namely the ability to adapt structurally and functionally, as well as the readiness of its human resources in public services and civil society